2020
DOI: 10.11591/ijeecs.v17.i3.pp1210-1214
|View full text |Cite
|
Sign up to set email alerts
|

A malicious URLs detection system using optimization and machine learning classifiers

Abstract: <span>The openness of the World Wide Web (Web) has become more exposed to cyber-attacks. An attacker performs the cyber-attacks on Web using malware Uniform Resource Locators (URLs) since it widely used by internet users. Therefore, a significant approach is required to detect malicious URLs and identify their nature attack. This study aims to assess the efficiency of the machine learning approach to detect and identify malicious URLs. In this study, we applied features optimization approaches by using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Ozcan et al [89] proposed hybrid DL models that were combinations of deep NN (DNN)-LSTM and DNN-Bidirectional LSTM (BiLSTM). They used two datasets from Ebbu2017 [90] and PhishTank [14], along with a dataset from PhishStorm [91]. They have extracted the network-based and lexical features.…”
Section: ) Lexical and Network-based Features Studiesmentioning
confidence: 99%
“…Ozcan et al [89] proposed hybrid DL models that were combinations of deep NN (DNN)-LSTM and DNN-Bidirectional LSTM (BiLSTM). They used two datasets from Ebbu2017 [90] and PhishTank [14], along with a dataset from PhishStorm [91]. They have extracted the network-based and lexical features.…”
Section: ) Lexical and Network-based Features Studiesmentioning
confidence: 99%
“…true-positives). The result showed that 31detected cases were erroneously labeled and agreed with [75]- [77] as false-positive; Also, 776 wrongly detected threats (i.e. false-negative) and 283-correctly recognized malicious instances labeled as true-negative.…”
Section: B Discussion Of Findingsmentioning
confidence: 99%
“…However, ground truth is not always available for training [71]- [74]. FS consists of two modes/classes, namely the filter and the wrapper [75], [76].…”
Section: Feature Selection (Fs)mentioning
confidence: 99%